Comparison of foot pressure distribution and foot kinematics in undulatory underwater swimming between performance levels - Koga, D.; Nakazono, Y.; Tsunokawa, T.; Sengoku, Y.; Kudo, S.; Takagi, H. (Sports Biomechanics, 2025)
This study aimed to elucidate the foot kinematics and foot pressure difference characteristics of faster swimmers in undulatory underwater swimming (UUS). In total, eight faster and eight slower swimmers performed UUS in a water flume at a flow velocity set at 80% of the maximal effort swimming velocity. The toe velocity and foot angle of attack were measured using a motion capture system. A total of eight small pressure sensors were attached to the surface of the left foot to calculate the pressure difference between the plantar and dorsal sides of the foot. Differences in the mean values of each variable between the groups were analysed. Compared to the slower swimmers, the faster swimmers exhibited a significantly higher swimming velocity (1.53 ± 0.06 m/s vs. 1.31 ± 0.08 m/s) and a larger mean pressure difference in the phase from the start of the up-kick until the toe moved forward relative to the body (3.88 ± 0.65 kPa vs. 2.66 ± 1.19 kPa). The faster group showed higher toe vertical velocity and toe direction of movement, switching from lateral to medial at the time of generating the larger foot pressure difference in the up-kick, providing insight into the reasons behind the foot kinematics of high UUS performance swimmers.